A mixed-methods examination of clinicians’ perceived barriers to telehealth delivered applied behavior analysis - Pomales-Ramos, Anamiguel; Tokish, Hannah; Howard, Mya; Straiton, Diondra; Ingersoll, Brooke (Frontiers in Psychology, 2023)
Following the COVID-19 pandemic, clinicians relied on telehealth to ensure continuity of essential healthcare services, such as Applied Behavior Analysis (ABA). Identifying barriers and examining them in the context of other implementation outcomes is important to support appropriate adaptations and sustainability of telehealth-delivered ABA services. Convergent mixed methods design was utilized to identify barriers experienced by ABA clinicians (N= 388) when delivering ABA services over telehealth to autistic children and their families following the first six months of the COVID-19 pandemic. Additionally, barriers were examined in relation to telehealth implementation outcomes and intentions for continued adoption. Findings reveal that clinicians rated providing direct services (M= 3.52, SD= 1.14) as more difficult than conducting assessments (M= 3.29, SD= 1.06), and both as more difficult than providing parent-mediated interventions [(M= 2.47, SD= 1.11), F(2, 381)= 162.26, p< 0.001]. A principal components analysis indicated a 3-factor solution of barriers related to:(1) technology (α= 0.82), (2) administrative tasks (α= 0.88), and (3) client characteristics (α= 0.88). The most frequently endorsed barriers were related to client characteristics, including increased difficulty providing telehealth services to children who elope (M= 4.37, SD= 0.81), children who exhibit challenging behaviors (M= 4.31; SD= 0.83), and children who are in the preverbal stage or use nonverbal language to communicate (M= 4.07; SD= 1.00). Fewer barriers related to client characteristics uniquely predicted implementation variables including acceptability, appropriateness, and feasibility. Thematic analysis revealed challenges related to technology, caregiver involvement, child engagement, implementation of intervention strategies over telehealth, and administrative or logistical barriers. These findings highlight the need for targeted strategies that facilitate telehealth use to address specific client needs and support the implementation of telehealth services in usual care settings.